Acclimation to high CO2 in maize is related to water status and dependent on leaf rank - Anneke P; Muchwesi Mukubi J; Pellny, Till K.; Verrier PJ; Beyenne G; Silva Lopes, M.; Emami K; Treumann A; Lelarge-Trouverie C; Noctor G; Kunert, Karl J.; Foyer, Christine H. (Wiley, 2011)
The responses of C3 plants to rising atmospheric CO2 levels are considered to be largely dependent on effects exerted through altered photosynthesis. In contrast, the nature of the responses of C4 plants to high CO2 remains controversial because of the absence of CO2-dependent effects on photosynthesis. In this study, the effects of atmospheric CO2 availability on the transcriptome, proteome and metabolome profiles of two ranks of source leaves in maize (Zea mays L.) were studied in plants grown under ambient CO2 conditions (350 +/− 20 µL L−1 CO2) or with CO2 enrichment (700 +/− 20 µL L−1 CO2). Growth at high CO2 had no effect on photosynthesis, photorespiration, leaf C/N ratios or anthocyanin contents. However, leaf transpiration rates, carbohydrate metabolism and protein carbonyl accumulation were altered at high CO2 in a leaf-rank specific manner. Although no significant CO2-dependent changes in the leaf transcriptome were observed, qPCR analysis revealed that the abundance of transcripts encoding a Bowman–Birk protease inhibitor and a serpin were changed by the growth CO2 level in a leaf rank specific manner. Moreover, CO2-dependent changes in the leaf proteome were most evident in the oldest source leaves. Small changes in water status may be responsible for the observed responses to high CO2, particularly in the older leaf ranks.